Economic and social rights after the global financial crisis - Nolan, Aoife (Cambridge : Cambridge University Press, 2014)
The global financial and economic crises have had a devastating impact on economic and social rights. These rights were ignored by economic policy makers prior to the crises and continue to be disregarded in the current'age of austerity'. This is the first book to focus squarely on the interrelationship between contemporary and historic economic and financial crises, the responses thereto, and the resulting impact upon economic and social rights. Chapters examine the obligations imposed by such rights in terms of domestic and supranational crisis-related policy and law, and argue for a response to the crises that integrates these human rights considerations. The expert international contributors, both academics and practitioners, are drawn from a range of disciplines including law, economics, development and political science. The collection is thus uniquely placed to address debates and developments from a range of disciplinary, geographical and professional perspectives.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Economic policy; Social rights; Global Financial Crisis, 2008-2009.